Genetic Variation of Hampala Fish (Hampala macrolepidota) Population in PB. Soedirman Reservoir and Serayu River - Suhestri Suryaningsih; Sorta Basar Ida Simanjuntak; Sri Sukmaningrum (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Panglima Besar Soedirman waters reservoir and the Serayu River in Banjarnegara Regency, Central Java is one of the habitats of hampala fish . Hampala fish is a member of the Cyprinidae family, which has economic value but is fully captured from the wild. The study on the genetic diversity using approaches of isozyme analysis needed to support conservation and domestication of the fish in this area. This study was aimed at the genetic variation of the hampala fish population in PB. Soedirman water reservoir and the Serayu River in Banjarnegara Regency based on esterase (EST), acid phosphatase (ACP), peroxidase (PER), and aspartate aminotransferase (AAT). Visualization of the isozyme was carried out employing horizontal electrophoretic technique with potato starch. From the results of this study it can be concluded that the hampala fish from the reservoir of PB. Soedirman, Serayu River area before reservoir and after reservoir, all of which are in Banjarnegara Regency, can visualized isozymes EST, ACP, and AAT well, except PER isozyme. This finding can be used as based information on population genetics and finally can be used for conservation of this fish. The results of this study are expected to be utilized to evaluate the potential genetic condition of hampala fish, which is the basis for conservation strategy and domestication.